Energy Efficiency and Health Efficiency of Old and New EU Member States - Feng, Yongqi; Yu, Xinye; Chiu, Yung-Ho; Lin, Tai-Yu (Frontiers in Public Health, 2020)
Environmental protection and health issues have always been of great concern. This study employed modified Meta-Frontier Dynamic Network Data Envelopment Analysis to explore the environment pollution effects from energy consumption on the mortality of children and adult, tuberculosis rate, survival rate and health expenditure efficiencies in 15 old EU states and 13 new EU states from 2010 to 2014. We calculated the overall efficiency scores and technology gap ratios for each old EU and new EU states, as well as the efficiencies of non-renewable energy, renewable energy, PM2.5, CO2, labor, GDP, tuberculosis, child mortality, adult mortality, and health expenditure efficiency and survival efficiency at the health stage. The average annual overall efficiencies of the old EU states are higher than that of the new EU states. Whether in terms of energy efficiencies or health efficiencies, the inputs and outputs of the old EU states are always higher than that of the new EU states. Overall, developing countries in Eastern Europe are lagging behind in terms of energy and health efficiencies. At the same time, the efficiency of child mortality is lower than that of adult mortality, and the efficiency of PM2.5 is higher than that of CO2 in both old and new EU states.